Enhancing STEM career pathways: Outcomes of a pre-professional workshop series at a historically black college - Hodges, Amber; Bryant, Damon; Green, Christopher (American Journal of STEM Education, 2025)
This study evaluates the impact of a STEM pre-professional workshop series (STEM PPWS) designed to enhance self-efficacy, persistence, and graduate school readiness among underrepresented minority (URM) students at a historically Black college. Grounded in Social Cognitive Career Theory, the intervention consisted of sequential workshops on career development topics, including interviewing, personal statements, and identifying suitable research opportunities. A pretest‒posttest design was employed with three cohorts (N = 71) across multiple years. Results showed statistically significant gains in self-efficacy, persistence, and career aspirations. The greatest improvements were noted in personal statement and interviewing workshops. These findings underscore the importance of targeted, skill-based, and identity-affirming cocurricular programming in preparing URM students for postbaccalaureate STEM pathways.